ФИЗИК ЖАРАЁНЛАРНИ МОДЕЛЛАШТИРИШ АСОСИДА ПОЛИТЕХНИК ТАФАККУРНИ РИВОЖЛАНТИРИШ ИМКОНИЯТЛАРИ - Рўзиева, Д.С. (SCIENCE and SOCIETY, 2023)
The article presents the possibilities of developing the polytechnic thinking of students of higher educational institutions in the field of technology on the example of physics using the method of software modeling.